2009
DOI: 10.1074/jbc.m109.011999
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan Molecular Weight Is Controlled by UDP-N-acetylglucosamine Concentration in Streptococcus zooepidemicus

Abstract: The molecular weight of hyaluronan is important for its rheological and biological function. The molecular mechanisms underlying chain termination and hence molecular weight control remain poorly understood, not only for hyaluronan synthases but also for other ␤-polysaccharide synthases, e.g. cellulose, chitin, and 1,3-betaglucan synthases. In this work, we manipulated metabolite concentrations in the hyaluronan pathway by overexpressing the five genes of the hyaluronan synthesis operon in Streptococcus equi s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 42 publications
2
49
0
Order By: Relevance
“…This is then activated by an uridyltransferase to form the HA precursor. The finding that UDP-N-acetylglucosamine is limiting the synthesis of high chain molecular weight has been shown in a recent study [26]. Studies have also claimed that the depletion of UDP-N-acetylglucosamine could be responsible for inhibiting HA synthesis process [42].…”
Section: Bioprocess Strategiesmentioning
confidence: 92%
See 1 more Smart Citation
“…This is then activated by an uridyltransferase to form the HA precursor. The finding that UDP-N-acetylglucosamine is limiting the synthesis of high chain molecular weight has been shown in a recent study [26]. Studies have also claimed that the depletion of UDP-N-acetylglucosamine could be responsible for inhibiting HA synthesis process [42].…”
Section: Bioprocess Strategiesmentioning
confidence: 92%
“…In a recent study on Lactococcus lactis housing the cloned szhasA and szhasB gene, an inverse relationship between the ratio of HasA enzyme and UDP-glucose concentration to the molecular weight of HA was observed [25]. A very recent study on HA molecular weight control in the native Streptococcus zooepidemicus has been reported, where it was observed that the unavailability of precursor UDP-Nacetylglucosamine, is the critical factor determining the molecular weight of the polymer [26]. However, it still remains to be seen if the various fermentation conditions yielding different molecular weight HA, presented in literature consistently explain this finding.…”
Section: Introductionmentioning
confidence: 94%
“…Nielsen and coworkers reported that overexpression of genes involved in the precursor sugar pathway led to the production of high-molecular-weight HA (11). In addition, a fermentation study has demonstrated that enhanced ATP levels brought by changing fermentation parameters enhanced the production and improved molecular weight of HA, probably by increased fluxes of the sugar precursor pathways (12).…”
mentioning
confidence: 99%
“…The cell dry weight was quantified by filtering 15 ml of broth using 22-m nylon membranes (Millipore, Bedford, MA) and drying the samples at 60°C for 8 h. The concentration of glucose was determined via high-performance liquid chromatography (Agilent 1200 HPLC system) (as described in Ref. 34) using a Phenomenex Rezex RHM Monosaccharide H ϩ column (300 ϫ 7.8 mm; 8 m) and detected by Refractive index. Erythromycin production was determined via LC-MS using a Dionex UltiMate 3000 liquid chromatography system (Dionex, Sunnyvale, CA) coupled with an AB Sciex 4000 QTRAP mass spectrometer (AB Sciex, Ontario, Canada) as described in Ref.…”
Section: Methodsmentioning
confidence: 99%